Children's participation in practice: comparing the views of managers and practitioners in an early intervention and prevention programme. Issue 1 (4th March 2022) - Tierney, Edel; Rodriguez, Leonor; Kennan, Danielle; Devaney, Carmel; Brady, Bernadine; Canavan, John; Forkan, Cormac; Cassidy, Anne; Malone, Pat; McGregor, Caroline
Abstract : Purpose: Participation is the active involvement of children and young people in decision-making regarding issues that affect their lives. It is crucial in the context of child protection and welfare systems and how they respond to the needs of children and young people. The purpose of this paper is to report on the evaluation of child and family participation in an early intervention and prevention programme implemented by the Irish Child and Family Agency. It provides an analysis of a comprehensive, "whole organization" approach to understand how participation is embedded in policy and practice. Design/methodology/approach: This paper reports on a comparative qualitative case study of the perspectives of managers and practitioners about participation practice, identifying the facilitators and barriers, as well as their perspectives of the sustainability of participation within the agency and its partners. The authors draw on two complementary, theoretically informed studies evaluating participatory practice within the Agency using qualitative interviews with participants. Findings: Overall, managers and practitioners had a positive attitude towards participation and identified examples of best practices. Facilitators included training, access to resources and the quality of relationships. Challenges for meaningful participation remain, such as the need to engage, hard to reach populations. Differences were identified regarding how embedded and sustainable participation was. Originality/value: This paper provides a critical understanding of participation in practice and how to embed a culture of participation in child protection and welfare.